Legal Validity of Virtual Land Ownership under the Civil Code: A Comparative Analysis and Protection Framework - Achmad Billy Badruzzaman; Sofyan Arief; Yohana Puspitasari Wardoyo (Faculty of Law, University of Merdeka Malang, 2026)
Abstract: The metaverse and virtual land, exemplified by platforms like RansVerse, have evolved from speculative concepts into commercial infrastructure. However, this commercial reality outpaces Indonesia’s legal framework, which lacks explicit statutory recognition of virtual land as property. Using a normative-juridical method with statutory, conceptual, and comparative approaches, this study examines the contractual validity of virtual land transactions under Article 1320 of the Indonesian Civil Code, compares Indonesia's regulatory stance with the United States and the European Union, and identifies available dispute-resolution mechanisms. The findings indicate that virtual land transactions via smart contracts and NFTs satisfy the four elements of contract validity. Because cryptocurrency cannot serve as legal tender in Indonesia, these transactions are properly characterized as asset-exchange agreements under Article 1541. Comparatively, Indonesia relies on civil-code analogy, the United States on contractual Terms of Service, and the European Union on unified statutory instruments. Meanwhile, dispute resolution remains constrained by jurisdictional and evidentiary uncertainties. The study concludes that legal certainty requires dedicated legislation on digital-property registration and consumer protection.